Aktualisasi Demokrasi Pancasila dalam Kehidupan Berbangsa dan Bernegara - nur rohim yunus (Sosio-Didaktika: Social Science Education Journal, 2015)
Democracy, as well as a fundamental principle in virtually all countries, has also become principles in the country. Several typologies of democracy indicates a new pattern generated from the basic theory of democracy. Pancasila Democracy is essentially the norms regulating the conduct of the people’s sovereignty and the running state government, in the political, economic, social, cultural, and defense, for every citizen of the Republic of Indonesia, both at central and regional levels. The concept of Pancasila democracy excavated from the original values of the society that developed in Indonesia. Pancasila Democracy is a middle path that must be addressed wisely because it is a unifying alternative between Indonesia multicultural society. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i2.2815